Photoinduced green synthesis of silver nanoparticles with highly effective antibacterial and hydrogen peroxide sensing properties - Kumar V.; Gundampati R.K.; Singh D.K.; Bano D.; Jagannadham M.V.; Hasan S.H. (My University, 2025)
In this study, an eco-friendly and sustainable green route was employed for the synthesis of stable silver nanoparticles (AgNPs) using aqueous leaf extract of Euphorbia hirta (AEE) as both reducing as well as a stabilizing agent. The synthesis of AgNPs was confirmed by UV–visible spectroscopy which produced a prominent SPR band at λmax 425 nm after 25 min of sunlight exposure. The AgNPs thus synthesized were optimized using one factor at a time approach, and these optimized conditions were 25 min of sunlight exposure time, 5.0% (v/v) of AEE inoculum dose and 3.0 mM of AgNO3 concentration. The Field Emission Scanning Electron Microscopy (FE-SEM) and High Resolution Transmission Electron Microscopy (HRTEM) analysis confirmed the presence of spherical AgNPs with average size 15.5 nm. The crystallinity was determined by X-ray Diffractometer (XRD) and Selected Area Electron Diffraction (SAED) pattern. Chemical and elemental compositions were determined by Fourier Transformed Infrared Spectroscopy (FTIR) and Energy Dispersive X-ray Spectroscopy (EDX) respectively. The Atomic Force Microscopy (AFM) images with average roughness 1.15 nm represented the lateral and 3D topological characteristic of AgNPs. The AgNPs thus synthesized showed effective antibacterial activity against gram negative and gram positive bacteria as well as hydrogen peroxide sensing property with a minimum detection limit of 10− 7 M. © 2016